Peanut Variety Performance in Florida 2003-2006 - Barry L. Tillman; Daniel W. Gorbet; Mark W. Gomillion; J. McKinney; W. D. Thomas (EDIS)
SS-AGR-109, a 10-page illustrated report by B. L. Tillman, D. W. Gorbet, M. W. Gomillion, J. McKinney, and W. D. Thomas, provides data from University of Florida trials conducted at Gainesville (Citra) Marianna, and Jay research centers from 2003-2006. Includes tables showing performance in 2006, performance of runner market-type varieties 2003-2006, performance of Virginia market-type varieties 2003-2006, pod yield, and disease resistance of major peanut varieties. Originally published by the UF Department of Agronomy as Marianna NFREC Research Report 07-1, March 2007.